Analyser le discours de presse - Alice Krieg (Communication)
This article proposes a few pointers with regards to the discourse of the press that may well help the discourse analyst in approaching their first confrontation with a sample from the written press. After analyzing the specific positioning of the researcher towards their object, we examine the nature of what is to be read in newspapers. The discourse of the press appears as an object proper, not to be reduced to a reflection of public speech. It is characterized by polyphony and by the selection and transformation of the statements it carries. A minimal familiarity with professional journalistic practice is necessary in order to understand who a newspaper gives a voice to difference actors in the public sphere.